The fortified site of Leceia (Oeiras) In the context of the chalcolithic in portuguese Estremadura - Cardoso, João Luís (2015)
Research into the Chalcolithic period in the region of Lower Estremadura, south of Torres Vedras, western Portugal, has generated much new data from fortified sites and cemeteries. The lack, so far, of a thorough overview of this diverse body of information has hindered the definition of the Chalcolithic culture of the region. The economic, social and cultural transformation observed at sites with a long sequence beginning with the Late Neolithic, has never been analysed. The results obtained by the author in one of the most notable sites of the region, the fortified site of Leceia, near the town of Oeiras, are of particular interest. Seventeen excavation campaigns carried out since 1983 have provided a remarkable body of information. The characterization of other previously identified Chalcolithic groups in Portugal allow us to see how the Chalcolithic of Estremadura relates, at a regional level, with the cultural development to the north, the south, the hinterland and the coast. Of major importance to this discussion are the chronometric results obtained in Leceia. For the first time, the 36 radiocarbon dates and their subsequent statistical treatment have allowed us to establish absolute boundaries for the existing successive cultural phases of the Late Neolithic and the Early, Middle and Late Chalcolithic.